Teaching English Action Verbs to Young EFL Learners Through Video-Based Instruction: A Quasi-Experimental Study - Azimova, Muborak Nodir qizi (The Lingua Spectrum, 2026)
This research examines differences in teaching English action verbs to young EFL learners through video-based instruction compared to traditional methods. The study compares learning outcomes of students taught action verbs using videos with those who received traditional text-based instruction. A quasi-experimental research design was employed, involving an experimental and a control group. Participants were young learners aged 7–8 with beginner-level English proficiency (A1–A2), studying at private school “Ixlos” in Tashkent, Uzbekistan. Both groups completed pre-tests and post-tests to measure their knowledge of English action verbs. The experimental group received instruction supported by videos and visual demonstrations, while the control group was taught using traditional methods without video treatment. Reliability of the research instrument was checked through internal consistency analysis using JASP software. Results reveal that video-based instruction has a significant positive impact on students’ understanding and retention of English action verbs, contributing to improved vocabulary teaching strategies for young EFL learners and demonstrating the effectiveness of multimedia integration in foreign language education.